Preparation of heterostructured Cu-CeO2/SrTiO3 catalysts by rapid plasma exsolution for photothermal reverse water gas shift reaction - Zihe Zhu; Jun Zhou; Qinghao Li; Zhengrong Liu; Qinyuan Deng; Zilin Zhou; Cunxin Li; Lei Fu; Jiacheng Zhou; Haonan Li; Qiankai Zhang; Kai Wu (Journal of CO2 Utilization, 2024)
High catalytic performances of metal-semiconductor heterostructures have gained significant attention in recent years. However, developing fast and low-cost synthesis of multiphase heterojunction catalysts has long been a challenge. Herein, three phases of Cu-CeO2-SrTiO3-δ heterojunction catalyst are successfully synthesized by combining with sol-gel and rapid plasma exsolution method. Using dielectric barrier discharge plasma (DBD), Cu nanoparticles are exsolved and uniformly distributed on the surface of CeO2-SrTiO3-δ. This unique multiphase heterojunction catalyst exhibits superior performance in photothermal reverse water gas shift (RWGS) reactions. The yield of CO from this catalyst is impressive at 11.32 mmol g−1 h−1, 9 times greater than pure SrTiO3, and the selectivity for CO is high (99.95%). The enhanced activity is primarily attributed to the synergistic effect resulting from the incorporation of three phases of Cu nanoparticles, CeO2, and SrTiO3-δ, as well as their interfaces. The increase in oxygen vacancy sites in CeO2 enhances the adsorption of CO2, whereas the doping and exsolution of Cu help to broaden the light absorption range. A significant role is played by the localized surface plasmon resonance (LSPR) effect of Cu nanoparticles in promoting the catalytic performance of RWGS. This study demonstrates a simple and efficient method for fabricating multiphase heterojunction catalysts, providing new strategies for photothermal CO2 reduction.